Impact of Free Wi-Fi in Coffee Shops on Teenagers' Worship Practices: A Quantitative Study: Pengaruh Nongkrong Di Warung Kopi Free WIFI Terhadap Ketaatan Ibadah Remaja - Rafid , Muhammad Jawwad Ikbar; Romadlon, Dzulfikar Akbar (Indonesian Journal of Education Methods Development, 2023)
This quantitative research examines the influence of free Wi-Fi availability in coffee shops on teenagers' worship practices. Utilizing observation and questionnaires, the study finds that a substantial percentage of teenagers frequently use Wi-Fi for various tasks, social media access, and gaming. Interestingly, this frequent Wi-Fi usage is also associated with increased rates of prayer and fasting. Statistical analysis reveals a significant effect of free Wi-Fi in coffee shops on teenagers' observance of worship, with a p-value of 0.002 and the calculated f-value surpassing the critical f-table value. These findings highlight the potential impact of technology accessibility on religious behaviors within the community environment. Highlights: Wi-Fi accessibility and Teenagers: Investigating the Influence in Coffee Shops. Significant Impact of Free Wi-Fi on Teenagers' Worship Practices. Observance of Worship in Coffee Shops: A Quantitative Analysis Keywords: Free Wi-Fi, Coffee shops, Teenagers, Worship practices